Exploring shape memory alloys in haptic wearables for visually impaired people - Ghodrat, Sepideh; Sandhir, Preeti; Huisman, Gijs (Frontiers in Computer Science, 2023)
Wearable haptic assistive devices can provide tactile information to visually impaired people (VIP) to support independent living. However, electromechanical haptic feedback has a number of disadvantages, including hardware being relatively heavy, large, and producing excessive sound. Here, we present a design-driven investigation of the potential of shape memory alloy-based haptic feedback for VIP. We followed an iterative approach, focusing on hands-on material explorations, in which we identified challenges and subsequent solutions that designers of SMA-based wearable haptic assistive devices may be faced with when incorporating SMAs in their designs. We present several prototype iterations and an initial evaluation with VIP to offer insights into the potential of SMA-based wearable haptic devices for VIP.